Sunday Driver Mediates Multi-Compartment Golgi Outposts Defects Induced by Amyloid Precursor Protein - Du, Qianqian; Chang, Jin; Cheng, Guo; Zhao, Yinyin; Zhou, Wei (Frontiers in Neuroscience, 2021)
Golgi defects including Golgi fragmentation are pathological features of Alzheimer’ disease (AD). As a pathogenic factor of AD, amyloid precursor protein (APP) induces Golgi fragmentation in soma. However, how APP regulates Golgi outposts (GOs) in dendrites remains unclear. Given that APP resided and affected GOs movements, especially reversed the distribution of multi-compartment GOs (mcGOs), we investigated the regulatory mechanism of mcGOs movements in Drosophila larvae. Knockdown experiments showed the bidirectional mcGOs movements were cooperatively controlled by dynein heavy chain (Dhc) and kinesin heavy chain subunits. Notably, only Dhc mediated APP’s regulation on mcGOs movements. Further, by loss-of-function screening, the adaptor protein Sunday driver (Syd) was identified to mediate APP-induced alteration of the direction of mcGOs movements, and dendritic defects. Collectively, by elucidating a model of bidirectional mcGOs movements, we revealed the mechanism of APP’s regulation on the direction of mcGOs movements. It provides new insights into AD pathogenesis.